Perceived dysphonia by the clinician's and patient's viewpoint - Ugulino,Ana Celiane (2012)
PURPOSE: To verify the relationship between the clinician's vocal evaluation and vocal self-assessment and voice-related quality of life. METHODS: Participants were 96 individuals: 48 with vocal complaints and voice deviation (VCG), mean age of 51 years, with diagnosis and indication of voice therapy; and 48 with no vocal complaints and healthy voices (NVCG), mean age of 46 years. All participants answered the Voice-Related Quality of Life (V-RQOL) questionnaire, performed a vocal self-assessment and were submitted to auditory-perceptual analysis of voice. RESULTS: Mean V-RQOL scores were different between groups for all domains. Self-assessment results also showed differences between groups, which was not the case in the auditory-perceptual analysis of sustained vowel and connected speech, showing that the patient's perception was worse than the clinician's. There was correlation between the V-RQOL domains (Socio-emotional and Physical: 76.8%; Socio-emotional and Total: 90.8%; Physical and Total: 95.8%), as well as between the Socio-emotional (-52.9%), Physical (-43.1%) and Total (-52.2%) domains and the self-assessment. However, no correlation was found between auditory-perceptual analysis and self-assessment measures, except for a weak correlation between vocal self-assessment and auditory-perceptual analysis of the sustained vowel (33.3%). CONCLUSION: The clinician's perception does correspond to the individual's self-perception of his/her vocal quality and the impact of a voice deviation on his/her quality of life, but not directly. The individual's perception about his/her vocal quality and voice-related quality of life complements the clinician's perception regarding the overall degree of the voice deviation.